Gratitude as an enactment of democratic citizenship - N, Davids (South African Journal of Higher Education, 2016)
The absence of violence and widespread unrest strengthens the argument that the transition to democracy in post-apartheid South Africa was a relatively peaceful one. However, one has to question whether the current unacceptably high levels of protest action – often resulting in loss of lives - might be symptomatic of a transition that has not quite lived up to its promises of democracy, equality, equity and dignity. This article commences with an overview of the various educational attempts made to instil democratic citizenship. In showing that these attempts have only partially been fulfilled, the article draws attention to a few of the challenges besetting a post-apartheid citizenship. In considering how these challenges could be countered, the article continues with an exploration of two forms of gratitude – a debt account and a recognition account. The article concludes by arguing that in the interests of a just democracy, and vibrant democratic citizens, gratitude between the state and its citizens have to be balanced between mutual accounts of debt and recognition, and that the optimal space for this type of balance to be enacted and cultivated is within and across educational spaces.